2013
DOI: 10.1039/c2tb00081d
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake and gene delivery using layered double hydroxide nanoparticles

Abstract: The cellular uptake of narrowly dispersed LDH {[Mg 3 Al(OH) 8 ](CO 3 ) 0.5 } nanoparticles into the Mouse Motor Neuron (NSC 34) cell line has been studied. The effect of LDH concentration and incubation time on the cellular uptake was investigated using fluorescein isothiocyanate (FITC) labelled LDH nanoparticles. We observed that cellular uptake increases with the increased LDHs concentration and incubation time.Confocal laser microscopy and transmission electron microscopy reveal that 20 nm LDHs nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 41 publications
2
72
0
2
Order By: Relevance
“…162 The study revealed that cellular uptake was directly proportional to LDH concentration and incubation time. They also found that LDHs of 20 nm size were better at internalizing in the cell cytoplasm and cell nucleus; however, LDHs greater than 20 nm were internalized in the cell cytoplasm.…”
Section: -161mentioning
confidence: 99%
See 2 more Smart Citations
“…162 The study revealed that cellular uptake was directly proportional to LDH concentration and incubation time. They also found that LDHs of 20 nm size were better at internalizing in the cell cytoplasm and cell nucleus; however, LDHs greater than 20 nm were internalized in the cell cytoplasm.…”
Section: -161mentioning
confidence: 99%
“…They also found that LDHs of 20 nm size were better at internalizing in the cell cytoplasm and cell nucleus; however, LDHs greater than 20 nm were internalized in the cell cytoplasm. 162 …”
Section: -161mentioning
confidence: 99%
See 1 more Smart Citation
“…Choy et al [11] also found dose dependent uptake of LDH-FITC NPs by NIH 3T3 cells in the test concentration range (<45 lM). Li et al [50] reported concentration dependent uptake of 65 nm CO 3 LDH-FITC by NSC 34 cells in the concentration range of 6.25-100 lg/mL, where FITC was adsorbed onto the surface of CO 3 -LDH instead of intercalated into the interlayers.…”
Section: Dose-dependent Uptakementioning
confidence: 99%
“…This could be caused by several vague parameters without clear and consistent definition. The first one is NP size, which is normally characterised as the Z-average hydrodynamic diameter (measured by light scattering technology) [29,41,50] or the number average size (measured and statistically calculated from TEM or SEM images) [6,28]. The second term is the dose of nanoparticle.…”
Section: Introductionmentioning
confidence: 99%